Influence of Genotype on Antioxidant Activity and Phenolic Profile of Fennel Bulbs - Alfonso Rubio; Antonio López-Orenes; María A. Ferrer; Antonio A. Calderón (Agronomy, 2024)
Currently, fennel bulb is becoming a highly demanded and consumed vegetable due to its licorice flavor and health benefits. Although the chemical composition of fennel essential oil has been extensively studied, the nonvolatile bioactive compounds of fennel bulbs have drawn less attention. Here, the phenolic profile and the antioxidant activity in terms of DPPH radical scavenging activity, reducing power, chelating ability of ferrous ions, and inhibition of lipid peroxidation were analyzed using four different fennel hybrid genotypes and three different extraction solvents (methanol, aqueous-methanol, and hot water). Antioxidant activity results revealed significant variation amongst fennel varieties (>3-fold difference for DPPH and reducing power and >2.7-fold for the inhibition of lipid peroxidation), with methanolic extracts exhibiting the highest antioxidant activity. Total phenol content peaked in the aqueous-methanol extracts, exhibiting a 2-fold difference across fennel genotypes. HPLC–PDA/MS analyses identified high levels of caffeic acid derivatives in hot water extracts, particularly in the commercial genotype. The therapeutic benefits associated with these compounds make it reasonable to use detailed phytochemical screening in fennel breeding programs to obtain varieties with new functionalities and thus higher added value.